The Effect of Ownership Structure on Dividend Policy in The Manufacturing Companies - Sumartha, Evy (Jurnal Economia, 2016)
Abstract: The Effect of Ownership Structure on Dividend Policy in The Manufacturing Companies. Ownership structure; as independent variables in this research; is represented by institutional ownership and managerial ownership. This research also aimed to obtain evidence of moderation function of the concentration of ownership in the relationship between ownership structure and dividend policy. The dependent variable is dividend policy which is measured by Dividend Payout Ratio (DPR). There are 97 sample companies. Hypothesis testing is done by Moderating Regression Analysis (MRA) and panel regression analysis. The results of this research show that the concentration of ownership serves as a moderating variable on the relationship between ownership structure and dividend policy. Institutional ownership in companies that do not have a managerial ownership has a negative effect on Dividend Payout Ratio; while institutional ownership in companies that have a managerial ownership has a positive effect on Dividend Payout Ratio. Profitability and company size as a control variable has effect on dividend policy.Keywords: the concentration of ownership, institutional ownership, managerial ownership, ROA, company size, dividend payout ratioAbstrak: Pengaruh Struktur Kepemilikan Terhadap Kebijakan Dividen pada Perusahaan Manufaktur. Struktur kepemilikan sebagai variabel independen dalam penelitian ini diproksikan dengan kepemilikan institusional dan kepemilikan manajerial. Penelitian ini juga untuk mendapatkan bukti mengenai fungsi moderasi dari konsentrasi kepemilikan dalam hubungan antara struktur kepemilikan dan kebijakan dividen. Variabel dependen adalah kebijakan dividen yang diukur dengan Dividend Payout Ratio (DPR). Sampel yang diperoleh sebanyak 97 perusahaan selama tahun pengamatan. Pengujian hipotesis dilakukan dengan Moderating Regression Analysis dan analisis regresi data panel. Hasilnya menunjukkan bahwa konsentrasi kepemilikan berfungsi sebagai variabel moderating pada hubungan antara struktur kepemilikan dan kebijakan dividen. Untuk kepemilikan institusional pada perusahaan yang tidak mempunyai kepemilikan manajerial berpengaruh negatif terhadap Dividend Payout Ratio, sedangkan kepemilikan institusional pada perusahaan yang mempunyai kepemilikan manajerial berpengaruh positif. Kepemilikan manajerial berpengaruh positif terhadap Dividend Payout Ratio. Variabel kontrol profitabilitas dan ukuran perusahaan berpengaruh pula terhadap kebijakan dividen perusahaan.Kata Kunci: konsentrasi kepemilikan, kepemilikan institusional, kepemilikan manajerial, ROA, ukuran perusahaan, dividend payout ratio